2019
DOI: 10.1051/sm/2019018
|View full text |Cite
|
Sign up to set email alerts
|

Are masters athletic performances predictive of human aging in men and women?

Abstract: Human aging particularly after ∼70 years, is associated with declines in physical function and athletic performance, that are accelerated in part by age-associated declines in physical activity and exercise training. Because elite athletes maintain high levels of physical activity across the lifespan, older athletes (Masters) may present as a proxy for healthy human aging. Although longitudinal studies are most informative about human aging, there are substantial practical challenges to conducting longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…At the same time, determining when to retire from a professional athletic career is highly dependent on the individual's performance and, intuitively, biological age. Chronological age may also lack appropriateness in predicting the beginning of a decline in physical performance in athletes approaching the end of their professional careers (35).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, determining when to retire from a professional athletic career is highly dependent on the individual's performance and, intuitively, biological age. Chronological age may also lack appropriateness in predicting the beginning of a decline in physical performance in athletes approaching the end of their professional careers (35).…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted on young football athletes at the Real Madrid Football School and Baturetno Football School showed that athletes had poor knowledge about the nutritional and fluid requirements for young football athletes at the Real Madrid Football School and Baturetno Football School (Puspaningtyas et al, 2019). Apart from that, the age factor of 31-35 years until physiologically advanced, there was a decrease in body functions such as the cardiovascular and respiratory systems (Senefeld & Hunter, 2019) which are influenced by genetics, the cardiovascular system, exercise patterns, lifestyle, and body composition. Furthermore, professional athletes who experience Anterior Cruciate Ligament (ACL) injuries turn out to have a significant effect on decreasing aerobic fitness (De Almeida et al, 2018).…”
Section: Figure 2 Physical Condition (Vo2max) Of Pusaka Fc Club Ball ...mentioning
confidence: 99%
“…Rata-rata VO2 Max terendah terdapat pada kelompok usia 31-35 tahun. Pada usia tersebut secara fisiologis terjadi penurunan fungsi tubuh seperti sistem kardiovaskular dan respirasi (Senefeld & Hunter, 2019). Berdasarkan posisi, rerata VO2 Max terendah dimiliki kiper.…”
Section: Distribusi Persentase Lemak Tubuh Dan Vo2 Maxunclassified